Pharmacological effects and pharmaceutical dosage forms development of aloe vera - Almaamari, Jamal Nasser Saleh (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2021)
The Aloe Vera plant is one of the oldest plants used for thousands of years. Aloe Vera has been used as a herb that cures multiple diseases throughout history. The series of studies conducted in the past two decades shed light on the chemical properties and natural compounds that this plant contains, such as anthraquinone, amino acids, acemannan, aloesin, and glucomannan, which have diverse therapeutic effects. This review aimed at reviewing the pharmacological effects of aloe vera plant and its different pharmaceutical dosage forms. The data was collected from international published literature in PMID and Google Scholar. It is to conclude that the Aloe Vera has therapeutics effects such as anti-inflammatory, wound healing, anti-oxidation, anticancer, anti-tumor, antiulcer, antiviral and antibacterial, and anti-cholesterol. In addition, some pharmaceutical formulations of aloe vera such as suppositories, creams, gels, and tablets can be developed.